Multilocus inherited neoplasia allele syndrome (MINAS) in a Turkish cohort: molecular insights and clinical relevance for precision oncology - Bahsi, Taha; Seyhan, Serhat; Helvaci, Kaan; Demirci, Umut; Bilgetekin, Irem; Bayram, Selami; Ozturk, Mehmet Akif; Aydogan, Fatih; Keskin, Serkan; Pilanci, Kezban; Sener, Nur; Tatlı, Murat; et al. (Frontiers in Pharmacology, 2025)
BackgroundMultilocus Inherited Neoplasia Allele Syndrome (MINAS) describes individuals who harbor pathogenic or likely pathogenic (LP/P) germline variants in two or more distinct cancer predisposition genes. With the broader implementation of next-generation sequencing (NGS) and multigene panel testing, MINAS has been increasingly recognized.MethodsWe retrospectively evaluated 655 Turkish patients referred for hereditary cancer testing using two validated NGS panels. MINAS was defined as the presence of LP/P variants in at least two different genes.Results14 patients (2.13%) met the criteria for MINAS. An additional 156 patients (23.8%) had single-gene LP/P variants. MINAS cases accounted for 8.2% of mutation-positive individuals. These patients showed diverse tumor types. Common gene combinations included BRCA1+MUTYH and CHEK2+PALB2.ConclusionThis is the first MINAS-focused analysis from a Turkish cohort. Although uncommon, MINAS represents a significant subset of genetically high-risk individuals requiring tailored clinical management.